Character Education in Quran: Thematic Interpretation of QS Luqman: 12-19 and Its Relevance to Character Education by the National Ministry of Education - Deri Wanto; Jalwis Jalwis (Institut Agama Islam Negeri (IAIN) Curup, 2021)
In Surah Luqman Verses 12-19 contained the formulation of educational values primary of character education. Research on the content of the verse is necessary and compelling to instill character values in children and at the same time berate children from environmental influences. This study uses a qualitative strain with library research. The purpose is to know the values of character education contained in the Surah Luqman verses 12-19 and to determine its relevance to the character education of the Ministry of National Education. Content analysis is a method used for textual and language. This research carried out the three points of education as a reference in educating children. The points are Tawhid, Islamic laws, and moral education. Other results through this research are several methods used in instilling character values; (a) Method by example or qudwah Hashanah, (b) Method of story, and (c) Method of advice